Revealing the Educational Message in Surah Al Fatihah - Zeinul Ubbaidi; Lestari Budianto (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
The Qur'an is the word of God which was revealed to be a guide for human life in all its roles and aspects. In it, of course, there is a lot of wisdom and knowledge that people can study, especially those related to education. This research used a descriptive qualitative approach and intended to explore the wisdom and knowledge related to education mentioned in the Al Fatihah surah by relying on Teun A. Van Dijk's Discourse Analysis theory. The results of this study include: First, implicitly the verses in the Al Fatihah surah are educational verses, where Allah teaches humans to know who their God is and who they are. More than that, through this verse Allah also teaches how humans should position themselves before their Lord. Second, implicitly also the verses in the Al-Al Fatihah contain the basic principles of learning methodology. This research is limited to exploring the meaning of education in the Al Fatihah surah. Therefore, it is suggested that future research be able to examine the application of the meaning of education to the Al Fatihah surah for students.